2020
DOI: 10.3389/fmicb.2020.571847
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Contributes to Liver Fibrosis Impact on T Cell Receptor Immune Repertoire

Abstract: Gut microbiota (GM) modifies the intrahepatic immune microenvironment, but the underlying mechanisms remain poorly understood. Liver fibrosis-associated imprinting is predicted to be reflected in GM. This study investigated the link between GM and the intrahepatic T cell receptor (TCR) immune repertoire (IR), and whether GM modulates the intrahepatic immune microenvironment via TCR IR during liver fibrosis. We analyzed the correlation between GM and TCR IR during liver fibrogenesis. Accordingly, 16S rRNA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…Invasion of foreign pathogenic bacteria is one of the most important factors disrupting the intestinal microbiota. In this study, the intestinal microbiota was found to be significantly changed in SC- P. g mice, with a decrease in bacterial diversity, which is known to be associated with intestinal inflammation and hepatic diseases [ 35 ]. Bacteroidetes and Firmicutes are the dominant microbiota in the gut [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Invasion of foreign pathogenic bacteria is one of the most important factors disrupting the intestinal microbiota. In this study, the intestinal microbiota was found to be significantly changed in SC- P. g mice, with a decrease in bacterial diversity, which is known to be associated with intestinal inflammation and hepatic diseases [ 35 ]. Bacteroidetes and Firmicutes are the dominant microbiota in the gut [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis of the gut microbiota can promote liver fibrosis by regulating the activation of hepatic stellate cells via the TCR IR-mediated intrahepatic immune environment (Liang et al, 2020). R e s t o r i n g t h e n o r m a l g u t m i c r o b i o t a v i a f e c a l transplantation can reduce liver fibrosis via remodeling of the intrahepatic TCR IR, a reduction in B cells, and an increase in CD8+ T cells (Novobrantseva et al, 2005;Guidotti et al, 2015;Liang et al, 2020). In addition, a study by Xu et al found that Schistosoma japonicum-induced liver fibrosis could be alleviated by suppressing the helper T cell 2 immune response and improving gut microbiota dysbiosis (Xu et al, 2020).…”
Section: Effect Of Altered Gut Microbiota On Liver Fibrosismentioning
confidence: 99%
“…The liver is a central immune organ. The gut microbiota and associated metabolites reach the liver via the intestinal barrier gaps with portal blood flow, and these are involved in the liver fibrosis process via Toll-like receptors (TLRs), nucleotide-binding oligomerization domain-like receptor (NLR)-mediated innate immunity, and T cell receptor immune repertoire (TCR IR)-mediated adaptive immune pathways involved in liver fibrosis ( Seki and Schnabl, 2012 ; Mridha et al., 2017 ; Liang et al., 2020 ). The TLR family are transmembrane proteins on intrahepatic cells that activate the innate immune system by recognizing microbiota and metabolites from the intestine, of which, TLR2, TLR4, TLR5, TLR7, and TLR9 can be involved in liver fibrosis, with TLR4 currently being the most studied ( Seki et al., 2007 ; Seki and Schnabl, 2012 ; Chen et al., 2019a ; Lee and Suk, 2020 ).…”
Section: Gut Microbiota and Liver Fibrosismentioning
confidence: 99%
“…Alteration of the gut microbiota determines the balance of translocation of the antigenic components thereby affecting the liver immune system. For example, dysbiosis caused by a hepatic fibrosis model in mice can reset the TCR immune repertoire (IR) and decrease their diversity that in turn reduces the number of different antigens they can recognize [57]. Additionally, the balance of endotoxins and exotoxins translocated to the liver can determine the immune response of the innate-like nature of some T cell subsets.…”
Section: T Cells and The Gut-liver Axismentioning
confidence: 99%